Effectiveness of Balloon Angioplasty in Children With Recurrent Aortic Coarctation Depends on the Type of Aortic Arch Pathology. (30th June 2016) - Herzog, Stefanie; Dave, Hitendu; Schweiger, Martin; Hübler, Michael; Quandt, Daniel; Kretschmar, Oliver; Knirsch, Walter
Abstract : Objectives: The aim of this study was to evaluate the effectiveness of balloon angioplasty (BAP) for recurrent aortic coarctation (ReCoA) in infants comparing simple and complex type of aortic arch pathology (Norwood I procedure). Background: ReCoA is a known complication after cardiovascular surgery for coarctation of the aortic arch. Methods and Results: In a single center case study, we analyzed 20 infants undergoing BAP for ReCoA comparing simple (n = 10) and complex type of aortic arch pathology (n = 10). At catherization diameter of ReCoA stenosis was 3.2 ± 0.7 mm (mean ± SD) with short localized (11/20) or long hypoplastic stenosis (9/20) before and 4.8 ± 1.2 mm after BAP (P < 0.001). Invasive systolic pressure gradient was reduced from 27.5 ± 16.2 mmHg before to 5.1 ± 6.6 mmHg after BAP (P   < 0.001), comparable in simple and complex type of ReCoA. At day 1 after catherization noninvasive systolic arterial blood pressure gradient was reduced from 20.2 ± 23.1 to 6.7 ± 9.9 mmHg (P   < 0.001), respectively, calculated continuous wave Doppler echo gradient from 36.3 ± 22 to 16.8 ± 9.6 mmHg (P   < 0.01). Complications were aortic arch dissection (1/20), discrete aortic arch aneurysm formation (1/20), pericardial effusion (1/20), and peripheral arterial thrombosis (4/20). At a mid‐term follow up of 9.5 months (1–40) after BAP, 3 infants needed early surgical reintervention due to secondary ReCoA, all with long hypoplastic aortic arch segments, but simple type of aortic arch pathology. Conclusions: At mid‐term follow up, BAP remains an effective catheter intervention for ReCoA for infants with localized ReCoA, but not with long hypoplastic aortic arch segments, even in simple type of aortic arch pathology.